PENGARUH LINGKUNGAN KERJA TERHADAP KEPUASAN KERJA KARYAWAN PADA RUMAH SAKIT LANCANG KUNING PEKANBARU - Ela Yanty; Ruzikna " (Jurnal Online Mahasiswa (JOM) Bidang Ilmu Sosial dan Ilmu Politik, 2014)
This study aimed to determine the effect of work environment on job satisfaction of employees in Lancang Kuning Hospital Pekanbaru. Work environment as an independent variable (X) has been formulated by the company service employees, working condition, employee relationship with the company. While job satisfaction as the dependent variable (Y). study was conducted on all employees Pekanbaru Lancang Kuning Hospital by 51 people. Data obtained from the questionnaire and further processed and then tested using statistical analysis such as a simple linear regression analysis, test, and correlation analysis and determiniasi using SPSS17. The results showed that the test results of hypothesis testing. tcount 5,25 >ttable 2,010. This suggests that the working environment affect the level of job satisfaction. The magnitude of the influence of environment on job satisfaction in Hospital amounted to 36%Keyword : work environment, job satisfaction, hospital